Ductal carcinoma in situ diagnosed by breast needle biopsy: Predictors of invasion in the excision specimen. (June 2016) - Doebar, S.C.; de Monyé, C.; Stoop, H.; Rothbarth, J.; Willemsen, S.P.; van Deurzen, C.H.M.
Abstract: Background: A substantial proportion of women with a pre-operative diagnosis of pure ductal carcinoma in situ (DCIS) has a final diagnosis of invasive breast cancer (IBC) after surgical excision and, consequently, a potential indication for lymph node staging. The aim of our study was to identify novel predictors of invasion in patients with a needle-biopsy diagnosis of DCIS that would help us to select patients that may benefit from a sentinel node biopsy (SNB). Patients and Methods: We included 153 patients with a needle-biopsy diagnosis of DCIS between 2000 and 2014, which was followed by surgical excision. Several pre-operative clinical, radiological and pathological features were assessed and correlated with the presence of invasion in the excision specimen. Features that were significantly associated with upstaging in the univariable analysis were combined to calculate upstaging risks. Results: Overall, 22% (34/155) of the patients were upstaged to IBC. The following risk factors were significantly associated with upstaging: palpability, age ≤40 years, mammographic mass lesion, moderate to severe periductal inflammation and periductal loss of decorin expression. The upstaging-risk correlated with the number of risk factors present: e.g. 9% for patients without risk factors, 29% for patients with 1 risk factor, 37% for patients with 2 risk factors and 54% for patients with ≥3 risk factors. Conclusion: The identified risk factors may be helpful to predict the upstaging-risk for patients with a needle-biopsy diagnosis of pure DCIS, which facilitates the performance of a selective SNB for high-risk patients and avoid this procedure in low-risk patients. Highlights: Predictors of invasion in patients with a needle-biopsy diagnosis of DCIS. These predictors would help us to select patients that may benefit from a sentinel node biopsy (SNB). Nodal staging could be avoided in patients with a low risk of invasion undergoing BCS. In patients with ≥1 risk factors, primary nodal staging by a SNB could be considered.